Flemish Expressionism : Belgium Today - 1980. - Schoonbaert, Lydia M. A., 1930-; The Tampa Museum, Tampa; High Museum of Art, Atlanta (Brussel : Ministerie van nationale opvoeding en Nederlandse cultuur, 1980)
Brusselmans, Jean ; Burssens, Jan ; De Saedeleer, Valerius ; De Smet, Gustave ; Ensor, James ; Jespers, Floris ; Landuyt, Octave ; Maas, Paul ; Malfait, Hubert ; Permeke, Constant ; Servaes, Albert ; Smits, Jacob ; Spilliaert, Leon ; Tytgat, Edgard ; Van den Berghe, Frits ; Van de Woestijne, Gustave
Flemish Expressionism, The Tampa Museum, Tampa, August 7 to September 8, 1980 ; High Museum of Art, Atlanta, October 3 to November 28, 1980
kunstcatalogus
Keywords: België